Creating a Web-Based Distro Clothes Sales Information System to Expand Market Share - Wahyu Eko Saputro (Indonesian Journal of Multidisciplinary Science, 2023)
The high competition in the clothing distro industry increasingly requires effective solutions to expand market share and increase sales. Along with the rapid development of information technology, the use of web-based sales information systems can be the right solution in facing this challenge. This research aims to develop a Web-based Clothing Distro Sales Information System to expand market share. This research uses applied research methods, while data collection techniques are carried out by observation, interviews and literature studies. The results showed that a web-based distro sales information system can help expand the distro's market share by increasing accessibility for potential buyers. With a web-based information system, prospective buyers can easily access information about products sold, prices, and available payment and shipping methods. In addition, this system can also provide convenience for buyers in making purchase transactions, such as online payments or ordering directly through the system and reaching more consumers from various regions that were previously difficult to reach.